HIV/AIDS and the public workplace : local government preparedness in the 1990s - Slack, James D., 1952- (University of Alabama Press, 1998)
"In this first empirical study of AIDS-related practices and attitudes in the workplace, James D. Slack analyzes in detail issues of reasonable accommodation and undue hardship as they apply to HIV/AIDS and the workplace and outlines the workplace costs of managing the epidemic."--BOOK JACKET. "The book concludes with specific recommendations about how management must empower itself to accept the primary responsibility for finding solutions to the workplace ramifications of HIV/AIDS. It also suggests concrete ways in which the federal government can assist management to empower itself."--BOOK JACKET.